SOME CLINICAL, SUB-CLINICAL CHARACTERISTICS AND QUALITY OF LIFE IN PATIENTS WITH FUNCTIONAL DYSPEPSIA - Dao Truong Giang; Pham Quang Phu; Tran Thi Thanh Phuong; Duong Xuan Nhuong (Tạp chí Y học Quân sự, 2026)
Objective: To describe some clinical characteristics, endoscopic lesions, H. pylori infection status, and assess quality of life in a group of patients with functional dyspepsia. Subjects and methods: A cross-sectional descriptive study of 160 patients with functional dyspepsia, examined and treated at the Gastroenterology Clinic, Military Hospital 103, from November 2024 to March 2025. Functional dyspepsia was diagnosed according to the Rome IV criteria. The severity of functional dyspepsia was assessed using the LDQ scale. Quality of life was assessed using SF-NDI. Results: The average age of patients with functional dyspepsia was 47.69 ± 15.13 years. Common clinical symptoms included epigastric pain (85.6%), postprandial fullness (73.1%), belching (63.1%), early satiety (55.0%), heartburn (54.4%), nausea (51.2%), and epigastric burning (50.6%). Gastroscopy revealed edematous and congestive lesions (74.4%) and flat and raised erosions (20.6%). 26.9% of patients were infected with H. pylori. According to the LDQ scale, the proportion of patients with moderate dyspepsia was 40.0% and severe dyspepsia was 31.9%. According to the SF-NDI, the proportion of patients experiencing significant impact on their quality of life was 58.8%. Conclusion: Functional dyspepsia has many clinical and sub-clinical manifestations, significantly affecting the quality of life of patients. Combining the assessment of disease symptoms and patient quality of life is essential in the management and treatment of patients with functional dyspepsia.